Existence and nonexistence of blow-up solutions for a Schrödinger equation involving a nonlinear operator - Zhang, Xinguang; Wu, Yong Hong; Cui, Y. (Elsevier, 2018)
By introducing a growth condition and using an iterative technique, we establish the results for the nonexistence and existence of positive entire blow-up solutions for a Schrödinger equation involving a nonlinear operator. Our main results improve and extend some existing works. In addition, we also give an example to illustrate our results.